Detachment of epitaxial graphene from SiC substrate by XUV laser radiation. (May 2020) - Vozda, V.; Medvedev, N.; Chalupský, J.; Čechal, J.; Burian, T.; Hájková, V.; Juha, L.; Krůs, M.; Kunc, J.
Abstract: The thermal decomposition on silicon carbide (SiC) is one of the most used growth techniques for fabrication of epitaxial graphene. However, it significantly diminishes graphene's otherwise exceptional carrier mobility. Reduction of the substrate influence is therefore essential for keeping conductivity at high levels. Here we present a novel technique where a sample with epitaxial graphene grown on SiC was exposed to intense 21.2 nm radiation. A sub-nanosecond pulse at low fluence in an interval 0.4–0.7 J/cm 2 was used to break covalent sp 3 bonds between the SiC substrate and buffer (the first graphene layer) which remains, except for release of its intrinsic strain, almost unaffected. A detailed analysis of the irradiated area examined by several microscopic and spectroscopic methods such as white-light interferometry and micro-Raman spectroscopy shows a clear evidence of a graphene layer detached from the substrate. Higher fluences induce damage to SiC substrate which expands due to the amorphization process. Damage thresholds were obtained by an advanced method of ablative imprints and compared with those calculated by the hybrid code XTANT. Graphical abstract: Image 1